Impact of bridging with left ventricular assist device on right ventricular function following heart transplantation - Annika Ingvarsson; Grunde Gjesdal; Saeideh Borgenvik; Anna Werther Evaldsson; Johan Waktare; Oscar Braun; Gustav J. Smith; Anders Roijer; Göran Rådegran; Carl Meurling (ESC Heart Failure)
Abstract Aims Patients awaiting orthotopic heart transplantation (OHT) can be bridged utilizing a left ventricular assist device (LVAD) that reduces left ventricular filling pressures, decreases pulmonary artery wedge pressure, and maintains adequate cardiac output. This study set out to examine the poorly investigated area of if and how pre‐treatment with LVAD impacts right ventricular (RV) function following OHT. Methods and results We prospectively evaluated 59 (LVAD n = 20) consecutive OHT patients. Transthoracic echocardiography (TTE) was performed in conjunction with right heart catheterization (RHC) at 1, 6, and 12 months after OHT. RV function TTE‐parameters included tricuspid annular plane systolic excursion (TAPSE), systolic tissue velocity (S′), fractional area change, two‐dimensional RV global longitudinal strain and longitudinal strain from the RV lateral wall (RVfree). At 1 month after OHT, the LVAD group had significantly better longitudinal RV function than the non‐LVAD group: TAPSE (15 ± 3 mm vs. 12 ± 2 mm, P < 0.001), RV global longitudinal strain (−19.8 ± 2.1% vs. −14.3 ± 2.8%, P < 0.001), and RVfree (−19.8 ± 2.3% vs. −14.1 ± 2.9%, P < 0.001). At this time point, pulmonary vascular resistance (PVR) was also lower [1.2 ± 0.4 Wood Units (WU) vs. 1.6 ± 0.6 WU, P < 0.05] in the LVAD group compared with the non‐LVAD group. At 6 and 12 months, no difference was detected in any of the TTE and RHC measured parameters between the two groups. Between 1 and 12 months, all parameters of RV function improved significantly in the non‐LVAD group but remained unaltered in the LVAD group. Conclusions Our results indicate that pre‐treatment with LVAD decreases PVR and is associated with significantly better RV function early following OHT. During the first year following transplantation, RV function progressively improved in the non‐LVAD group such that at 6 and 12 months, no difference in RV function was detected between the groups.